Effects of Electronic Tax Filing O Tax Compliance among Small and Medium Enterprises in Embu County, Kenya. - Kyungu, Hellen Mwongeli (University of Embu, 2019)
Small and medium-sized enterprises have been shown to play a very critical role in the Kenyan economy due to the fact that they provide employment opportunities to millions of Kenyans. The following research thus analyzed how the implementation of the e-tax system has influenced tax compliance on small and medium-sized enterprises in Embu County. The objective of the study was answered using three research questions which revolved around online registration and online tax filing and how each is affected by the online system in order to enhance compliance. The study seemed to analyze the impact of computer literacy has influenced online tax filing and how this reflects on tax compliance among small and medium enterprises in Embu. Keny The study also determined the perception and attitudes of inculcating a tax compliance culture oo potential future taxpayers at an early age and analyzed on the cost-effectiveness of e-tax system adoption among SME's. The research also explored several theories like the Fischer tax tax compliance model, the theory of planned behavior and diffusion of innovation theory that analyzed the compliance of individuals in filing their tax reports. The research also explored the empirical framework that has been conducted on similar researches. This research study, therefore, achieved its objectives by using questionnaires, and making observations. Data obtained were subjected to various quantitative and qualitative data analysis to evaluate the data from the respondents using SPSS (version 20). The results were presented in easily understandable formats such as the use of graphs and descriptive analysis tables. Both quantitative and qualitative results were presented in the most applicable format paving the way to making conclusions from the results and recommendations. All the respondents voted excellently (I 00%) e-tax system's involvement in increasing tax compliance by SMEs.